2011
DOI: 10.2175/193864711802721596
|View full text |Cite
|
Sign up to set email alerts
|

Ammonia Oxidizing Archaea, AOA, Population and Kinetic Changes in a Full Scale Simultaneous Nitrogen and Phosphorous Removal MBR

Abstract: We report unusually high nitrification activities at very low dissolved oxygen concentrations in a full-scale membrane bioreactor that operates with simultaneous nitrification denitrification and phosphorus removal, SNDP. We obtained a high affinity for oxygen in a nitrifying mixed culture population.. The calculated value for the half oxygen saturation coefficient was 0.01 mg/l, an order of magnitude lower than previously reported. This is the second independent report of these observations in full scale plan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…The discovery of nitrifiers from the genus archea (Giraldo et al, 2011) is raising the potential to design systems that will select and maintain these relatively slow growing organisms to enhance ammonia oxidation kinetics at low DO concentrations. Because of essentially zero TSS in the membrane treated effluent, the SRT can be simply controlled by wasting a desired portion of the MBR system volume daily without the need for MLSS or effluent TSS concentration measurements.…”
Section: Srt and Microbial Populationmentioning
confidence: 99%
See 1 more Smart Citation
“…The discovery of nitrifiers from the genus archea (Giraldo et al, 2011) is raising the potential to design systems that will select and maintain these relatively slow growing organisms to enhance ammonia oxidation kinetics at low DO concentrations. Because of essentially zero TSS in the membrane treated effluent, the SRT can be simply controlled by wasting a desired portion of the MBR system volume daily without the need for MLSS or effluent TSS concentration measurements.…”
Section: Srt and Microbial Populationmentioning
confidence: 99%
“…Work by Giraldo et al (2011) suggests that the nitrification kinetics are not appreciably slower at low DO conditions due to the selection of other organisms with more favorable kinetics. Other potentially attractive features of SND in MBR BNR processes are the elimination of separate preanoxic and postanoxic zones, the ability to operate with just one recycle line, and the ability to eliminate the need for a deoxygenation zone for the RAS flow.…”
Section: Research Needsmentioning
confidence: 99%
“…For instance, oxidation ditch-type reactors have been shown to achieve up to 50% total nitrogen removal in sections of the process with low aeration (Bertanza, 1997, Park et al, 2002. Membrane bioreactors have also been efficiently operated with low-DO to achieve SND (Giraldo et al, 2011, Littleton et al, 2013. More recent operational approaches such as ammonia-based aeration control (Amand and Carlsson, 2012, Amand et al, 2013, Rieger et al, 2014 have also been shown to effectively achieve SND at low-DO.…”
Section: Introductionmentioning
confidence: 99%
“…In continuous aeration, the SRT must be sufficiently long so that the DO setpoint required to meet the ammonia oxidation requirement (ammonia setpoint) is low enough for SND. This means that the SRT either needs to be increased to lower the DO setpoint, and/or that the nitrifying bacteria population needs to be adapted to achieve higher ammonia oxidation rates at lower DO concentrations (Giraldo et al., 2011; Keene et al., 2017; Park, Regan, & Noguera, 2002). In this study, in order for continuous aeration to achieve the same level of TIN removal as intermittent aeration, the SRT needed to be much longer.…”
Section: Discussionmentioning
confidence: 99%
“…While there are many studies on SND in extended aeration processes and oxidation ditches (Bertanza, 1997; Daigger & Littleton, 2000; Liu et al., 2010), membrane bioreactors (MBRs) (Giraldo, Jjemba, Liu, & Muthukrishnan, 2011; Hocaoglu, Insel, Ubay Cokgor, & Orhon, 2011), biofilms (Matsumoto, Terada, & Tsuneda, 2007; Randall & Sen, 1996) and granular sludge (Bassin, Kleerebezem, Dezotti, & van Loosdrecht, 2012; Kreuk, Heijnen, & van Loosdrecht, 2005), studies of SND in conventional plug‐flow type reactors are lacking. This distinction is important because extended aeration processes and MBRs typically carry high mixed liquor suspended solids (MLSS) and long solids retention times (SRTs) allowing for an endogenous carbon source and the ability to nitrify at very low DO.…”
Section: Introductionmentioning
confidence: 99%